Superprevodnost - Kos, Pavel (Matrika, 2014)
This article presents the main characteristics of superconductors. Firstly, magnetic properties are described. Then we take a closer look at the theory of superconductivity, where among other things, a simplified Cooper problem is solved. Then the emergence of an attractive potential due to phonon interactions is illustrated. In the end, some characteristic features of high-temperature superconductors are described.
Keywords: Cooper problem; Cooperjev problem; high-temperature superconductivity; superconductivity; superprevodnost; visokotemperaturna superprevodnost